(untitled) (Salduie, 2022)
In recent decades there have been a number of endeavours to re-examine women’s lives during the last Ice Age. For far too long, the view of ‘man-the-hunter’ and woman as ‘gatherer, cook and child minder’ was an unchallenged hypothesis, and without doubt, this simplistic view of early hunter-gatherer’s division-of-labour practices was ripe for revision. Unfortunately, it led to a number of over-zealous assertions: that women were big game hunters too, and as such, could not have been dominated by men. Breaking such stereotypes about prehistoric women is the message delivered in a recent documentary and accompanying book called ‘Lady Sapiens.’ But are such views about the roles of men and women in pre-history based on anything more than wishful thinking and result in fresh mythologising? Is there any archaeological evidence that allows us to assume anything about the economic activities of men and women in these early prehistoric cultures?